Saúde da pessoa em situação de rua: retratos psicossociais da vida na rua - Sousa, Francisco Annielton Borges (2019)
The research aimed to understand how to take care of the Family Health Strategy from the perception of professionals of the Family Health Strategy team as well as the homeless person. The study of homeless people allows a series of reflections on the positioning of the components of this group in today's society and, consequently, on the relationship of these subjects with the rest of the population. It is evident, however, the condition of poverty in which they live and the discriminatory treatment they receive from the public authorities and most of the city's inhabitants. The study is characterized by the descriptive exploratory nature, with qualitative approach. Participated in the survey: professionals from CSF Tamarindo and the homeless who are being accompanied by the POP Center, with broken family ties and no regular conventional housing. By approaching the professionals and the homeless population we can perceive the look on health care, with regard to health policies directed to this population that has so many particularities and complexities.